Control of the Survival and Growth of Human Glioblastoma Grafted into the Spinal Cord of Mice by Taking Advantage of Immunorejection. Issue 7 (July 2015) - Itakura, Go; Kobayashi, Yoshiomi; Nishimura, Soraya; Iwai, Hiroki; Takano, Morito; Iwanami, Akio; Toyama, Yoshiaki; Okano, Hideyuki; Nakamura, Masaya
Recent studies have demonstrated that transplantation of induced pluripotent stem cell-derived neurospheres can promote functional recovery after spinal cord injury in rodents, as well as in nonhuman primates. However, the potential tumorigenicity of the transplanted cells remains a matter of apprehension prior to clinical applications. As a first step to overcome this concern, this study established a glioblastoma multiforme xenograft model mouse. The feasibility of controlling immune suppression to ablate the grafted cells was then investigated. The human glioblastoma multiforme cell line U251 MG was transplanted into the intact spinal cords of immunodeficient NOD/SCID mice or into those of immunocompetent C57BL/6J H-2kb mice treated with or without immunosuppressants [FK506 plus anticluster of differentiation (CD) 4 antibody (Ab), or FK506 alone]. In vivo bioluminescent imaging was used to evaluate the chronological survival of the transplanted cells. The graft survival rate was 100% ( n = 9/9) in NOD/SCID mice, 0% ( n = 6/6) in C57BL/6J mice without immunosuppressant treatment, and 100% ( n = 37/37) in C57BL6/J mice with immunosuppressant treatment. After confirming the growth of the grafted cells in the C57/BL6J mice treated with immunosuppressants, immune suppression was discontinued. The grafted cells were subsequently rejected within 3 days in C57BL/6J mice treated with FK506 alone, as opposed to 26 days in C57BL/6J mice treated with FK506 plus anti-CD4 Ab. Histological evaluation confirmed the ablation of the grafted cells. Although this work describes a xenograft setting, the results suggest that this immunomodulatory strategy could provide a safety lock against tumor formation stemming from transplanted cells.